(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the official structure of oaths used in Uzbek and their use in English, their linguistic and morphological features, the use of official oaths in various fields, and their importance are consistently stated. that is, the synonyms of the word oath are the words vow and swear, and the explanatory dictionaries of the English language explain that the word oath is an official promise to do something or an official statement confirming the truth of something.